2020
DOI: 10.1002/ghg.2027
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the role of caprock morphology on history matching of Sleipner CO2 plume using an optimisation method

Abstract: Geological carbon storage is a promising solution to reduce the CO2 concentration in the atmosphere to ameliorate the effects of global warming from the greenhouse effect. Among feasible storage options, deep saline aquifers are believed to have the largest storage capacity for the gas collected from industrial processes. The first CO2 storage project at a commercial scale in a saline aquifer is in the Sleipner field of the Utsira storage formation in Norway. The long ongoing storage operation in the Sleipner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…While the impact of CO2 impurity on plume migration was negligible, the study showed that raising the average storage site temperature to 46 o C improves the history matching results. A recent history matching study on Sleipner 2019 benchmark model (Ahmadinia, M.& Shariatipour, 2020) showed an improvement of around 8% in the plume match resulted by an absolute elevation calibration of 3.23 meters in the caprock. Calibrating porosity, permeability, CO2 density and injection rate all together resulted in 5% improvements in the match, and once caprock elevation was adjusted too, the match increased by 16%.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of CO2 impurity on plume migration was negligible, the study showed that raising the average storage site temperature to 46 o C improves the history matching results. A recent history matching study on Sleipner 2019 benchmark model (Ahmadinia, M.& Shariatipour, 2020) showed an improvement of around 8% in the plume match resulted by an absolute elevation calibration of 3.23 meters in the caprock. Calibrating porosity, permeability, CO2 density and injection rate all together resulted in 5% improvements in the match, and once caprock elevation was adjusted too, the match increased by 16%.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadinia and Shariatipour [89,90] found that slight variation of the topography of the interface between the caprock and the upper reservoir, within the aforementioned limits on seismic resolution, led to substantial improvement in the agreement between Darcy flow simulations and the observations of plume distribution.…”
Section: Internal Barriersmentioning
confidence: 99%
“…A good storage candidate will have a secure and very low permeable caprock (extremely tight formation), a large pore volume, good permeability and good pressure connectivity over long distances so the injection will not result in a significant pressure build‐up 38 . Moreover, several parameters, including the presence and size of structural traps, 25,39 the planned amount of injected CO 2 40,41 , likely migration paths, 39 migration speed 42 and the pressure build‐up, 43,44 must be taken into account while characterising a potential storage reservoir 27 . Based on the structural characteristics of the site, the lateral and vertical migration of the CO 2 can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…88 The results showed that the plume development has two stages, the first occurring in the full thickness of the aquifer and the second at the top of the site. Several studies have investigated the effect of the caprock on the overall carbon storage process in realistic 8,28,29,41 and synthetic [24][25][26][27][89][90][91] models. The effect of tilt, permeability anisotropy and rugosity, namely the roughness of the surface, with the main focus on the aquifer and caprock interface, were studied previously.…”
mentioning
confidence: 99%